Errors of Omission in Outpatient Prescriptions in Jordan - Al Awawdeh, Safaa; Naddaf, Ahmad; Abuirmeileh, Amjad (Jordan Journal of Pharmaceutical Sciences, 2018)
Introduction: Prescription errors are one of the most common forms of medical errors that can occur at any point during drug therapy. This includes prescribing, transcribing, dispensing, administering, and monitoring. Errors of omission in prescriptions involves the absence or incomplete specification of dosage form or strength, dose or dosage regimen and quantity or duration of drug to be supplied. Illegiblity of prescriptions and prescriptions that violate legal requirements are also considered errors of omission. Objectives: The aim of this study was to analyze the prescription errors in a Jordanian community pharmacy setting in order to detect the most frequent errors of omission that expose people to potential risks of medication errors. Methods: An audit retrospective study was conducted for screening prescriptions. 800 prescriptions were randomly selected as a study sample. The duration of this study was 8 months and in collaboration with one of largest chain pharmacies in Jordan. Data collection was carried out using a checklist form and later analyzed using Graphpad prism software version 5.0. Results: Results show that the percentage of errors of omission in prescription writing related to transcriber’s and patient information were high where errors related to prescriber’s name reached 17%, prescriber’s signature 11.5%, patient name 12%, patient age 62%, patient sex 97.25% , prescription Date 16.5%, illegibility 2.75% and incomplete prescriptions 59.75%. The percentage of errors related to drug’s information errors included missing dosage form 54.75%, missing unit of strength 26.25%, missing frequency 8.5%, missing duration of treatment 96.75%, unauthorized abbreviation 5%, illegible prescriptions 25.75% and incomplete prescriptions 68.25%. Conclusion: The reviewed prescriptions suffered serious deficiencies and improper writing. The findings clearly indicate that there were asignificant errors of omission in the chosen pharmacy setting which reflects negative quality of health care.